(untitled) (Annals of Bangladesh Agriculture, 2021)
Forty-three candidate restorer lines of Brassica napus were evaluated for 11 agronomic traits for genetic variability and interrelationships among yield traits to find out yield contributing traits. A wide range of variability and character association was observed among the lines. The line BNR-017 took the lowest time for first (26.67 days) and 100% flowering (41.00 days) whereas BNR-031 (74.33 days) and BNR-034 (74.00 days) matured earlier. The lines BNR-022 (1.07m) and BNR-026 (1.02m) were found with the shortest plant stature and all other lines were in average plant height of around 1.35m. The lines BNR-039, BNR-011, BNR-001, BNR-013 and BNR-014 were found the best performer for number of pods per plant, seeds per pod and seed yield per plant. Estimates of genotypic and phenotypic coefficient of variation were high (≥30%) for seed yield per plant (30.52 and 33.13, respectively). High broad sense heritability was recorded for 1000-seed weight (97.69%), days to ripening (97.12%), days to first flowering (96.80%), days to 100% flowering (95.50%) and pod length (92.74%). Significant and negative correlation was observed between seed yield per plant and number of seeds per pod, -0.217* and -0.192*, respectively both at genotypic and phenotypic level, while the highest positive and significant genotypic (0.786**) and phenotypic (0.795**) correlation were found with pod length. Path co-efficient analysis showed the highest positive and direct phenotypic effect of number of seeds per pod (1.221) on seed yield per plant while days to first flowering had the maximum negative direct effect (-0.039). The results of genotypic and phenotypic coefficient of variation, heritability and genetic advance in percent of mean, correlation co-efficient and path coefficient revealed that pods per plant, pod length, seeds per pod and 1000-seed weight could be used as selection criteria to increase seed yield in rapeseed. Ann. Bangladesh Agric. (2020) 24(1) : 51-64